THE INFLUENCE OF LAW 12.431 OF 2011 ON ENCOURAGED DEBENTURE SPREAD - Nunes, Rodolfo Vieira; dos Santos, Agostinho Moura; Sales, George André Willrich (RC&C: Revista de Contabilidade e Controladoria, 2021)
Applying resources in the infrastructure is vitally important for the expansion of national infrastructure. The government enacted Law No. 12.431/2011, which provides for income tax exemption for individuals residing in Brazil or foreigners who invest in debentures related to the infrastructure projects implementation (encouraged debentures). Thus, it is expected that the tax benefit, granted by the Law, will be one of the determining factors in the pricing of debentures, since, by the rational choice theory, it seeks to test the hypothesis that the spread required for encouraged debentures is equivalent to the spread of any other debenture of the same level of risk adjusted for the income tax fiscal impact. However, the results do not show that the spread of encouraged debentures is lower than the spread of non-encouraged debentures. The research contribution addresses questions about government sectorial public policies and the characteristics of the debentures market in Brazil, the research showed a new outlook on this investment market in recent years.